Short-Axis Methyl Substitution Approach on Indacenodithiophene: A New Multi-Fused Ladder-Type Arene for Organic Solar Cells - Li, Yun; Wang, Menghan; Wu, Fupeng; Gao, Xuyu; Huettner, Sven; Tao, Youtian; Jiang, Zuo-Quan (Frontiers in Chemistry, 2019)
Indacenodithiophene (IDT) is a promising building block for designing organic semiconductors. In this work, a new pentacyclic ladder-type arene IDMe was designed and synthesized by introducing methyl substitution on the short-axis of IDT. Two non-fullerene electron acceptors (IDIC and ID-MeIC) without and with methyl substitution were designed and synthesized for further study. Compared with IDIC, ID-MeIC with methyl substitution on the short-axis of IDT shows smaller bandgap, stronger extinction coefficient, and better crystallinity. Besides, PBDB-T: ID-MeIC blend film shows more efficient exciton generation and dissociation and more balanced charge transport mobility. Therefore, polymer solar cells based on PBDB-T: ID-MeIC can achieve better photovoltaic performance with a PCE of 6.46% and substantial increase in JSC to 14.13 mA cm−2 compared to 4.94% and 9.10 mA cm−2 of PBDB-T: IDIC. These results suggest that short-axis substitution on multi-fused ladder-type arenes, such as IDT is an effective way to change the optical and electronic properties of the organic semiconductors for high-performance OPVs.